Sosialisasi Keselamatan Berlalu Lintas di Jalan Raya untuk Warga SMA Negeri 2 Kahayan Tengah - Desi Riani; Salonten; Sutan Parasian Silitonga; Desriantomy; Robby; Supiyan; Murniati; Ina Elvina; Devia; Raden Haryo Saputra (Fakultas Teknik Universitas Palangka Raya, 2023)
SMAN 2 Kahayan Tengah is one of the schools located in Bukit Rawi, Pulang Pisau Regency, Central Kalimantan Province. In the school there are 150 students, most of whom have used motorised vehicles to get to school and pass through the highway. The purpose of this service is to provide knowledge and is expected to increase the awareness of citizens of SMAN 2 Kahayan Tengah towards traffic rules, signs and markings that apply on the highway. The method of activity implementation is in the form of socialization / lecture. The results of this community service can be seen from the results of questions and answers, interviews and fun quiz, there is a fairly good increase in terms of knowledge and understanding of students regarding traffic rules, signs and markings.